Pesticide Mode of Action Classification: Understanding Resistance Action Committees (RACs) - Emily C. Kraus; Brett Bultemeier (EDIS)
This publication defines the concept of a pesticide mode of action and provides several examples. It emphasizes the importance of identifying and differentiating modes of action for pesticide resistance management. To this end, it defines the development and goals of the three Resistance Action Committees for insecticides (IRAC), herbicides (HRAC), and fungicides (FRAC) and describes each group’s pesticide mode of action classification scheme. Finally, it provides an example of a pesticide label and instructs applicators on how to rotate pesticides to manage resistance. This publication presents the subject matter in a concise manner and directs pesticide applicators to the very useful RAC Mode of Action group numbers for rotation purposes.